High-Precision combinatorial deposition of micro particle patterns on a microelectronic chip - Löffler, Felix; Wagner, Jennifer; König, Kai; Märkle, Frieder; Fernández, Simón; Schirwitz, Christopher; Torralba, Gloria; Hausmann, Michael; Lindenstruth, V.; Bischoff, F. Ralf; Breitling, F.; Nesterov, A. (Aerosol science and technology, 2011)
The behavior of charged bio polymer micro particles when deposited onto a CMOS chip can be analytically modeled in form of the incompressible Navier-Stokes equation and the electrostatic Poisson equation, as we describe in this article. Based on these models, numerical simulations of depositions can be implemented in COMSOL that lead to improvements in the experimental setup, optimizing the size and charge distribution of the micro particles. Adapting the experiments according to the simulation results, we will show the powerful gain in deposition precision, which is essential for a contamination-free deposition and hence high quality combinatorial deposition.
Gesehen am 20.09.2022